Tumors of the Brain and Spine - DeMonte, Franco; Gilbert, Mark R.; Mahajan, Anita; McCutcheon, Ian E.; Buzdar, Aman U.; Freedman, Ralph S.; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Our rapidly increasing knowledge about tumors of the brain and spine has rendered these tumors more treatable than ever before. In the new world of central nervous system oncology, maximally complete resection is followed by conformal radiotherapy and often by chemotherapy, the selection of which is based on the tumor$1 (Bs susceptibility to drugs that have biological actions known to interact with the tumor$1 (Bs particular molecular signature. The chapters of this book collectively weave a tapestry depicting the range of medical, surgical, and radiotherapeutic approaches to neuro-oncology as it is practiced at M. D. Anderson Cancer Center, along with the diversity of disciplines needed for effective therapy. M. D. Anderson faculty describe their current approaches to patient assessment, decision making, and management of central nervous system tumors, including treatment for either palliation or for cure. Tumors of the Brain and Spine is the sixth book in the M. D. Anderson Cancer Care Series. This book, like the others in this series, highlights integrated care and focuses on treating the patient through the entire spectrum of the disease. This thorough, practical volume, which includes more than 70 illustrations and 30 tables, is an essential clinical guide for oncologists, surgeons, and other health care providers involved in the care of patients with central nervous system tumors.s
Epidemiology of Brain Tumors -- Neuropathology and Molecular Biology of Intracranial Tumors -- Radiology of Brain Tumors: Structure and Physiology -- Surgically Curable Brain Tumors of Adults -- Low-Grade Gliomas: Evidence-Based Treatment Options -- Surgical Strategies for High-Grade Gliomas -- Radiation Oncology for Tumors of the Central Nervous System: Improving the Therapeutic Index -- Cytotoxic Chemotherapy for Diffuse Gliomas -- Innovative Treatment Strategies for High-Grade Gliomas -- Pituitary Tumors in Oncology -- Management of Lung Cancer, Breast Cancer, and Melanoma Metastatic to the Brain -- Neoplastic Meningitis -- Lymphoma Affecting the Central Nervous System -- Tumors of the Extradural Spine -- Tumors of the Spinal Cord and Intradural Space -- Symptom Management for Patients with Brain Tumors: Improving Quality of Life.
Keywords: Medicine; Oncology; Neurology; Neurosurgery; Pathology; Surgical oncology; Medicine & Public Health; Neurology; Oncology; Surgical Oncology; Neurosurgery; Pathology; Electronic books